Human resource development (HRD) strategies for knowledge sharing in a higher learning institution - Shaari, Rozaiana; Alias, Rose Alinda (Penerbit UTM Press, 2007)

(untitled)
The process of knowledge sharing is not just for transmitting or transferring the knowledge but more on the value and the impact of the knowledge itself. Effective knowledge sharing can be achieved through a process of socialization within supportive organizational culture. However, people's non-supportive beliefs in sharing knowledge either formal or informal ways can cause knowledge management efforts fail in an organization. The objective of the. study is to understand the nature of sharing knowledge that will lead into the understanding of its awareness and readiness, focusing on its perceptions or views in an institute of higher learning. This paper presents the organizationaVmanagement views on knowledge sharing. A Multiple Perspective Framework (MPF) is used as a lens in understanding the phenomenon of study. Data are collected through interviews with academicians in a public higher learning institution. This study uses the content analysis methodology in analyzing the data. A total of nine items, served as indicators or factors of management's views on knowledge sharing. The HRD strategies are recommended based on these items.